1991
DOI: 10.1128/jb.173.23.7557-7564.1991
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the upstream activating sequence and site of carbon and nitrogen source repression in the promoter of an early-induced sporulation gene of Bacillus subtilis

Abstract: The transcription from the spoVG promoter of Bacillus subtilis is induced at the start of the stationary phase of growth and is dependent on the expression of the spoOA, spoOB, and spoOH genes. It is repressed in cells grown in the presence of excess glucose and glutamine and is under the negative control of the abrB gene. The spoOA and spoOB gene products function to suppress the negative control exerted by abrB. Transcription initiation requires the form of RNA polymerase holoenzyme that contains the spoOH g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
30
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…AbrB-dependent repression is exerted at a site which includes an A-T-rich sequence (upstream-activating sequence) that lies immediately upstream of the spoVG promoter (14,46 (12,62); however, this expression is now spoOA-abrB independent (12). Transcription of spoVG is also repressed when cells are cultured in sporulation medium supplemented with high concentrations of glucose and glutamine (12), which are preferred carbon and nitrogen sources, respectively. This control, termed Ggr (glucose-glutamine-dependent repression), is exerted downstrean of the site of abrB-dependent repression and within a region which includes the spoVG promoter (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AbrB-dependent repression is exerted at a site which includes an A-T-rich sequence (upstream-activating sequence) that lies immediately upstream of the spoVG promoter (14,46 (12,62); however, this expression is now spoOA-abrB independent (12). Transcription of spoVG is also repressed when cells are cultured in sporulation medium supplemented with high concentrations of glucose and glutamine (12), which are preferred carbon and nitrogen sources, respectively. This control, termed Ggr (glucose-glutamine-dependent repression), is exerted downstrean of the site of abrB-dependent repression and within a region which includes the spoVG promoter (12).…”
mentioning
confidence: 99%
“…These serve to repress abrB (41,50), which negatively (50,51) controls spoVG transcription (14,46,63,64). AbrB-dependent repression is exerted at a site which includes an A-T-rich sequence (upstream-activating sequence) that lies immediately upstream of the spoVG promoter (14,46 (12,62); however, this expression is now spoOA-abrB independent (12). Transcription of spoVG is also repressed when cells are cultured in sporulation medium supplemented with high concentrations of glucose and glutamine (12), which are preferred carbon and nitrogen sources, respectively.…”
mentioning
confidence: 99%
“…The relationship between these regulators and the nutritional response is obscure, however. Some genes subject to such regulation, such as spoVG (12), are required for sporulation, but others, such as aprE (8), amyE (25), and gsiA (23), are not. The hut (histidine utilization) operon (1,26) and the citB gene (5,10), which encodes aconitase, are also induced early in stationary phase and are repressed independently by a mixture of amino acids and by rapidly metabolizable carbon sources.…”
mentioning
confidence: 99%
“…Excess glucose in the growth medium represses sporulation, and some of the effects on sporulation have been linked to specific repression of H activity (1,7,8,16,17,50,52). The crsA47 mutation renders sporulation resistant to repression by glucose (49).…”
mentioning
confidence: 99%
“…A variety of experiments have shown that the increase in H activity as measured by transcription of H -dependent genes does not match the accumulation of the H protein, implying the existence of posttranslational controls (8,16,17,21,23,45,50). Furthermore, evidence has been presented that external pH (8) and the activity of the tricarboxylic acid cycle (26) affect H activity and that H protein levels are affected by a Lontype protease during the onset of sporulation and during stress responses (30).…”
mentioning
confidence: 99%